Penerapan Teknologi Tepat Guna Mesin Pencacah Pada Kelompok Peternak Di Desa Sei Mencirim, Deli Serdang – Sumatera Utara - Hermawan, Indra; Noviandri, Dian; Yolanda, Agnita; Darianto, Darianto; Iswandi, Iswandi (CV. IRA PUBLISHING, 2023)
Feed is a vital element crucial to supporting the growth and survival of livestock. Forages, commonly known as livestock fodder, serve as the primary food source for animals and form the foundation of livestock development efforts. Sei Mencirim Village has a livestock farmers' group named